Pendampingan Konservasi Koleksi Di Museum Sang Nila Utama Pekanbaru - Bunari, Bunari; Fikri, Asyrul; Surya Barkara, Refli; Michelle Angel, Aurora; Khoryah Sari, Nur (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
Many collections are stored at the Sang Nila Utama Museum, even hundreds of years old. This collection varies from basic materials. Ten categories, Biology, Geology, Ethnography, Ceramology, History, Philology, Archaeology, Technology, Heraldry and Fine Arts, are used by the Snag Nila Utama Museum to categorize the types of collections. Of course, maintaining such a large collection requires proper handling, conservation and storage techniques. Of course, one museum has differences in its methods of conservation and preservation of its collections. This activity focuses on discussing the application of techniques used by the Sang Nila Utama Museum in maintaining or preserving its collections. This activity serves to preserve and maintain collection objects to make them more durable and not easily eroded by time. So that historical objects will be well preserved to continue to be preserved for future generations from generation to generation.